Dairy Products, Dietary Calcium, and Risk of Inflammatory Bowel Disease: Results From a European Prospective Cohort Investigation. Issue 6 (June 2016) - Opstelten, Jorrit L.; Leenders, Max; Dik, Vincent K.; Chan, Simon S. M.; van Schaik, Fiona D. M.; Khaw, Kay-Tee; Luben, Robert; Hallmans, Göran; Karling, Pontus; Lindgren, Stefan; Grip, Olof; Key, Timothy J.; et al.
Abstract : Background: Dairy products may be involved in the etiology of inflammatory bowel disease by modulating gut microbiota and immune responses, but data from epidemiological studies examining this relationship are limited. We investigated the association between prediagnostic intake of these foods and dietary calcium, and the subsequent development of Crohn's disease (CD) and ulcerative colitis (UC). Methods: In total, 401, 326 participants were enrolled in the European Prospective Investigation into Cancer and Nutrition cohort. At recruitment, consumption of total and specific dairy products (milk, yogurt, and cheese) and dietary calcium was measured using validated food frequency questionnaires. Cases developing incident CD (n = 110) or UC (n = 244) during follow-up were matched with 4 controls. Conditional logistic regression analyses were used to calculate odds ratios (ORs) with 95% confidence intervals (CIs), adjusted for total energy intake and smoking. Results: Compared with the lowest quartile, the ORs for the highest quartile of total dairy products and dietary calcium intake were 0.61 (95% CI, 0.32–1.19, ptrend = 0.19) and 0.63 (95% CI, 0.28–1.42, ptrend = 0.23) for CD, and 0.80 (95% CI, 0.50–1.30, ptrend = 0.40) and 0.81 (95% CI, 0.49–1.34, ptrend = 0.60) for UC, respectively. Compared with nonconsumers, individuals consuming milk had significantly reduced odds of CD (OR 0.30, 95% CI, 0.13–0.65) and nonsignificantly reduced odds of UC (OR 0.85, 95% CI, 0.49–1.47). Conclusions: Milk consumption may be associated with a decreased risk of developing CD, although a clear dose-response relationship was not established. Further studies are warranted to confirm this possible protective effect. Abstract : Article first published online 27 April 2016.